Healing of full thickness chondral defects treated with arthroscopic subchondral bone plate microfracture and IL-1ra / IGF-1 delivered through gene transfer - Morisset, Sophie, author; Frisbie, David, advisor; Nixon, Alan, committee member; Powers, Barbara, committee member; McIlwraith, Wayne, committee member (Colorado State University. Libraries, 2003)
Hyaline articular cartilage is a specialized tissue that needs an intact structure to perform its physiologic functions. Once damaged, cartilage typically heals with fibrocartilage and fibrous tissue. These tissues do not possess the biomechanical and biochemical properties of the original hyaline cartilage, and therefore compromise the integrity of the articular surface and affect normal joint function. Various techniques have attempted to improve healing of cartilage defects. So far, no single method has clearly shown advantages over the others. Previous work in our laboratory has that a technique; arthroscopic subchondral bone plate microfracture (SBPM) increases the amount of repair tissue present in the defect and improved the quality of cartilage repair by increasing the amount of type II collagen but, was unable to up regulate the synthesis of proteoglycans. This project was performed to evaluate if the intra-articular injection of adenoviral vectors carrying the equine genes of interleukin-1 receptor antagonist (IL-1ra) and insulin-like growth factor-I (IGF-1) would enhance the healing of experimentally created cartilage defects treated with SBPM. Using an equine model of full thickness chondral defect the effects of gene transfer of AdEqIL-1ra and AdEqIGF-1 on cartilage healing was evaluated. Results of the study demonstrated an up-regulation of IL-1ra expression for a period of 21 days and an increased endogenous production of IGF-1 for a period greater than six weeks. These increases in protein expression were associated with improvements in the biochemical composition of the repair tissue. Repair tissue in defects of treated joints showed an increased amount of proteoglycans and type II collagen content as demonstrated by biochemical and immunohistological analyses. This study was able to show that gene transfer of an anabolic growth factor and an anti-inflammatory molecule can successfully be used to enhance cartilage healing in the horse and will hopefully bring us a step closer to effectively modulate the production of long lasting functional repair tissue.
Keywords: surgery; medicine